КОНТРОЛЬ СТУПЕНЯ РОЗПУШЕННЯ КРАЙНІХ ПАКЕТІВ ЗУБЦЕВОЇ ЗОНИ ОСЕРДЯ СТАТОРА ТУРБОГЕНЕРАТОРА З ЗАСТОСУВАННЯМ ЄМНІСНОГО СЕНСОРА - Левицький, А.С.; Новік, А.І.; Федоренко, Г.М. (Інститут електродинаміки НАН України, Київ, 2013)
The capacitive method of control of degree of loosening of hatch-end packages of tooth zone of stator core of power turbo generator is proposed. It is shown that loosening is related to initiation of gas intervals between the sheets of package Control is carried out at overlapping of capacitive sensor on loosening package over the layer of dielectric. Sensor is the system of alternating highly-potential and low-potential parallel coplanar electrodes. A calculation model is developed and all components of electric capacitance of sensor are determined. These components is presented as dependences, relating sizes of sensors, thickness of isolating dielectric layer between surface of sensor and surface of package, and size of gaps between the sheets of package. It is shown that information about appearance of loosening is a change of one of components of electric capacity of sensor. Analytic dependences which have been obtained in this paper can be used for designing of real industrial device. References 8, figures 4.